Metal–Organic Frameworks: A New Class of Lasing Materials: Intrinsic Stimulated Emission from Nonlinear Optically Active Metal–Organic Frameworks (Adv. Mater. 17/2017). Issue 17 (May 2017) - Medishetty, Raghavender; Nalla, Venkatram; Nemec, Lydia; Henke, Sebastian; Mayer, David; Sun, Handong; Reuter, Karsten; Fischer, Roland A.
Abstract : Stimulated emission as the new intrinsic property of metal–organic frameworks is demonstrated in article number1605637 by Roland A. Fischer and co‐workers, by the observation of stimulated emission peak, and time‐resolved photoluminescence, along with the support of density of state calculations. The results identify that immobilization of strong luminescent chromophores between the metal‐nodes leads to the formation of the materials with enhanced stability and optical behavior for the next generation solid‐state lasers.